Effect of sound radiation from plate attached with absober - Yusoff, Adnan (2015)
In everyday life, engineering widely used into solve and assistance people, whether medical, developmental, industrial processing, manufacturing, transportation and others. In the meantime, engineering must be made up of a system to allow it to work well for rapidity, efficiency as well as get the exact results. For the example in development of aerospace industries demands the use of lightweight materials, such as thin panels. However, thin panels have potential to contribute to substantial vibration and sound radiation, which lead to excessive noise. So, the study was carried out by determine the sound pressure radiated from simply support plate (SSP) without absorber and compared with attached single absorber in term of vibration reduction. Later, the study was investigate the effect of mass and damping coefficient also need to optimize the location of absorber. Then, investigation of the effectiveness of using multiple absorbers carried out. The study found that the numerical simulation works by ANSYS® and analytical analysis by MATLAB ® have error less than 105 which negligible. The frequency range used are 0 Hz to 200 Hz and there are a number of modes show. The mass and damping in the absorber have investigated for the effectiveness. The mass of 1 kg more suitable for use as a percentage reduction of vibration is the highest of 98.3921%. The damping values of 20 kg/s shows that the percentage reduction in the amplitude of the vibration is 98.5112%. Further, this study was undertaken by placing the absorber at different locations configuration. This was followed by the addition of a single absorber and multiple absorber to see the average percentage reduction in vibration and the results show the highest usage of absorber better absorption of vibration which is single absorber with 99.9395% and four absorber with 99.6048%. Finally, it can be concluded that multiple vibration absorber can reduce the overall global vibration compared to a single absorber and the structure that takes into account the weight of the dynamic vibration absorber is not suitable to be implemented due to the excessive weight of the structure will result in less fuel efficiency in vehicles, aerospace, automotive systems and machines also for the human healthty.